Effect of ultrasound on subserosal and intramural fibroids in vitro: A quasi-experimental study of physical therapy - El-Touny, Enas Said; Youssef, Amel Mohamed; El-deeb, Abeer Mohamed; Abd El Hameed, Raafat Ezz Eldeen; Kamal , Hosam-eldin Hassein; Ewais, Najlaa Fathi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to determine the effect of ultrasound (US) on extra subserosal and intramural uterine fibroids in vitro. A quasi-experimental, randomized, pre-post intervention study of physical therapy was conducted. Thirty women, who underwent myomectomy for subserosal or intramural fibroids with any leiomyomas’ volumes in the operating room of Bab El-Sharia Hospital, participated in the study. Thirty uterine fibroids whose were collected from participants were randomly divided into three groups (I, II and III), and exposed to ultrasound therapy for 15, 30, and 45 minutes respectively. Leiomyomas volumes were measured using the fluid displacement method before and after the application of US. The samples were kept in saline solution immediately after their excision from operating room to be transferred to physical therapy department in same hospital to apply ultrasound therapy. Results of all study groups (I, II, and III) showed a statistically significant decrease in the volume of subserosal and intramural leiomyoma post US application (p>0.05). However, there was no statistically significant difference in the size of the subserosal and intramural leiomyoma between study groups (p<0.05). In conclusion, the ultrasound therapy is effective in shrinking the volume of subserosal and intramural leiomyomas without effect of long duration ultrasound therapy.